The consequences of fermentation metabolism on the qualitative qualities and biological activity of fermented fruit and vegetable juices - Shah Saud; Tang Xiaojuan; Shah Fahad (Food Chemistry: X, 2024)
Fermentation of fruit and vegetable juices with probiotics is a novel nutritional approach with potential health benefits. Lactic acid fermentation-based biotransformation results in changes in the profile and nature of bioactive compounds and improves the organoleptic properties, shelf life and bioavailability of vitamins and minerals in the fermented juices. This process has been shown to enrich the phenolic profile and bioactivity components of the juices, resulting in a new type of functional food with improved health benefits. Fruits and vegetables are the ideal substrate for microbial growth, and fruit and vegetable juice will produce rich nutrients and a variety of functional activities after fermentation, so that the high-quality utilization of fruits and vegetables is realized, and the future fermented fruit and vegetable juice products have a wide application market. This paper explores the typical fermentation methods for fruit and vegetable juices, investigates the bioactive components, functional activities, and the influence of fermentation on enhancing the quality of fruit and vegetable juices. The insights derived from this study carry significant implications for guiding the development of fermented fruit and vegetable juice industry.